The Influence of Financial Literacy, Life Style, Social Class, and Online Shopping Fashion on Consumptive Behavior: Pengaruh Financial Literacy, Life Style, Social Class, dan Online Shopping Fashion Terhadap Perilaku Konsumtif - Megawati Cucu Sumantri; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
This research purpose to know the influence of financial literacy, life style, social class, and online shopping fashion on consumptive behavior at the advocate office of A.F KAPLALE & ASSOCIATES SIDOARJO. The instrument used was a questionnaire to obtain research data. This research uses validity test and reliability test. The hypothesis is that there is an the influence of financial literacy, life style, social class, and online shopping fashion on consumptive behavior. The analytical tool used to test the hypothesis is SPSS version 18. The test results based on the validity test show that all the questions on the questionnaire are valid. While the test results using the reliability test of all variables have a Cronbach's alpha value > 0.6 which means that it is reliable. The results of hypothesis testing in the form of T-Statistic and R-Square state that there is a positive influence between financial literacy, life style, and social class on consumptive behavior, while online shopping fashion has a negative effect. This is shown from the results of tcount for the Financial Literacy variable (X1) of 2.070, the Life Style variable (X2) of 2.214, the Social Class variable (X3) 2.406 and the Online Shopping Fashion variable (X4) of -2.223